Dynamic Response and Failure Mechanism of Deep-Buried Tunnel with Small Net Distance under Blasting Load - Jianjun Shi; Wenxiang Xu; Hao Zhang; Xinyan Ma; Huaming An (Buildings, 2023)
Under blasting load, a series of safety problems, such as lining cracking and surrounding rock instability, are prone to occur in deep-buried tunnels with a small net distance. It is significant to understand the dynamic response and failure mechanism of tunnels under blasting. The blasting attenuation formula is optimized through theoretical analysis and field experiments. The measuring point vibration is monitored in real time and the tunnel blasting model is established by ANSYS/LS-DYNA software. The model was set as having no reflective boundary and an uncoupled charge structure was used. The attenuation law of blasting seismic waves is studied from the adjacent tunnel lining and the direction of the tunnel cross-section and length. The inner and outer sides of the tunnel lining are investigated, respectively. The displacement and acceleration of lining measuring point are also analyzed. The dynamic response of the tunnel lining under blasting excavation is analyzed from multiple angles. The results show that the arch foot on the inner side of the lining (the side in contact with the tunnel headroom) is the first to generate vibration. On the outside of the lining (the side in contact with the rock),the peak vibration velocity is reached after blasting load unloading. There is little difference in the vibration velocity at different positions of the transverse section, but great difference in the vibration velocity of the longitudinal section. The influence of the horizontal displacement was greater than that of the vertical displacement. The vibration acceleration of the measuring point at the arch foot of the section is the largest and the detonation is also the largest.